2003
DOI: 10.1124/jpet.102.041756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Nicotinic Ligand Exposure on Function of Heterologously Expressed, Human α4β2- and α4β4-Nicotinic Acetylcholine Receptors

Abstract: Effects of prolonged nicotinic ligand exposure on the function of human ␣4␤2-and ␣4␤4-nicotinic acetylcholine receptor (nAChR) subtypes were studied using receptors heterologously expressed in SH-EP1 human epithelial cells. Magnitudes of acute, nAChR-mediated, specific 86 Rb ϩ efflux responses to 1 mM carbamylcholine were reduced after pretreatment with specific nAChR ligands in effects that depended on pretreatment drug dose, duration of drug pretreatment, and duration of drug-free recovery. Fifty percent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Furthermore, evidence from pharmacokinetic studies of nicotine (for review, see Benowitz et al, 1989;Henningfield and Keenan, 1993;Mathieu-Kia et al, 2002) suggests that periods of abstinence (i.e., when an individual attempts to quit smoking) could cause some desensitized nAChRs to recover function. Consistent with this suggestion, Gentry et al (2003) demonstrated that desensitized nAChRs can recover function in the absence of nicotine in vitro. These receptor-level changes could account for the behavioral tolerance demonstrated by mice treated chronically with nicotine and for deficits in contextual fear conditioning demonstrated by mice withdrawn from chronic nicotine in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, evidence from pharmacokinetic studies of nicotine (for review, see Benowitz et al, 1989;Henningfield and Keenan, 1993;Mathieu-Kia et al, 2002) suggests that periods of abstinence (i.e., when an individual attempts to quit smoking) could cause some desensitized nAChRs to recover function. Consistent with this suggestion, Gentry et al (2003) demonstrated that desensitized nAChRs can recover function in the absence of nicotine in vitro. These receptor-level changes could account for the behavioral tolerance demonstrated by mice treated chronically with nicotine and for deficits in contextual fear conditioning demonstrated by mice withdrawn from chronic nicotine in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…In addition to numerous studies conducted with native nAChRs, nicotine-induced upregulation has also been examined extensively in heterologous expression systems, including both Xenopus oocytes [267,268] and cultured cell lines [267,[269][270][271][272][273][274][275]. Such studies have helped to confirm that nicotineinduced upregulation is a post-transcriptional event and that it may occur by a mechanism consistent with nicotine acting as a molecular chaperone [276].…”
Section: Nicotine-induced Up-regulation Examined With Recombinant Nachrsmentioning
confidence: 99%
“…The apparent decrease in receptor function produced by chronic ligand exposure may arise from ligand-induced persistent desensitization or inactivation of nAChRs (Peng et al, 1994;Gentry et al, 2003). However, it is also possible that the population of receptors that are increased by nicotine treatments remain in intracellular compartments such that receptors at the plasma membrane are unaltered or even reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, primary neurons in culture chronically treated with nicotine up-regulate nAChRs (Bencherif et al, 1995;Nashmi et al, 2003;Lomazzo et al, 2011;Govind et al, 2012). Few studies have addressed the resulting functionality of the receptors expressed on neurons in primary culture after prolonged agonist exposure, although nAChR function has been measured after chronic nicotine exposure in cells expressing ␣4␤2-nAChRs heterologously (Peng et al, 1994;Gopalakrishnan et al, 1996;Buisson et al, 2000;Gentry et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation